Epidemiological Investigation of Bovine Ephemeral Fever Outbreaks in Israel. (26th July 2010) - Yeruham, Israel; Van Ham, Michael; Stram, Yehuda; Friedgut, Orly; Yadin, Hagai; Mumcuoglu, Kosta Y.; Braverman, Yehuda
Abstract : Outbreaks of bovine ephemeral fever (BEF) occurred in Israel in 1990, 1999, and 2004. The main patterns of BEF spread were similar in the 1990 and in 1999 epidemics, and the BEF virus was probably carried in vectors transported by air streams across the Rift Valley and the Red Sea. In the 2004 outbreak, the primary focus of the disease was the southern Mediterranean coastal plain and the disease agent was apparently brought by infected mosquitoes carried from their breeding site in the Nile Delta by the south-western winds. The disease broke out under optimal ecological conditions, among a vulnerable cattle population and spread rapidly; it showed essentially a spring-summer herd incidence and terminated soon after the night average ambient temperature fell below16 ∘ C in late autumn. The herd incidence of the disease reached 78.4%, 97.7%, and 100% in 1990, 1999, and 2004, respectively. The highest herd incidence, morbidity, and case fatality rates were noted in dairy cattle herds in the Jordan Valley, with morbidity of 20%, 38.6%, and 22.2%, and case fatality rate among affected animals of 2%, 8.6%, and 5.4% in 1990, 1999, and 2004, respectively. The average sero-positivity to BEF in 1999 was 39.5%, which matched the morbidity rate. Comparison among the various age groups showed that the lowest morbidity rates were observed in the youngest age group, that is, heifers up to 1 year, with 3.2%, 3.6%, and 4.2% in 1990, 1999, and 2004, respectively. In heifers from 1 year to calving, the morbidity rates were 13.8%, 14.9%, and 28%, respectively, in first calvers 30.8%, 31.6%, and 28.3%, respectively, and in cows 34.3%, 35.7%, and 27.2%, respectively. All affected cattle were over the age of 3 months. It is hypothesized that mosquitoes and not Culicoides spp. are the vectors of the BEF virus in Israel.